Wavefront aberrations in children with myopia and hyperopia before and after cycloplegia - E. P. Tarutta; S. G. Arutyunyan; T. S. Smirnova (Российский офтальмологический журнал)
Purpose: a comparative study of the effect of cycloplegia on wavefront aberration in children with myopia and hyperopia. Material and methods. The study involved 20 patients (39 eyes) with myopic refraction (averagely -5.2 ± 1,5 D) and 26 patients (52 eyes) with hyperopic refraction (averagely +3.1 ± 1.15 D), aged 5 to 17 (mean age 11.6 ± 0.6 years). All patients underwent wavefront aberrometry in a darkened room before and after a cycloplegic drug administration (1 % cyclopentolate dehydrochloride 2 times with an interval of 10 minutes, aberrometry 30 minutes after the first instillation) using the aberrometer OPD-Scan III, Nidek. Aberrations of the lower and higher orders were analyzed with a pupil 3 mm wide, both without and under cycloplegia (in the latter case, a 3 mm band was chosen). Total aberrations (RMS) were studied. Zernike coefficients were used to calculate the standard deviation of total higher order aberrations (RMS HOAs), the vertical and the horizontal tilt (C1-tilt1, C2-tilt2), the vertical and horizontal trefoil (C5-trefoil 6, C8-trefoil 9), the vertical and horizontal coma (C6-coma7, C7-coma8), and spherical aberration (S4 + S8 + S12). Results. Both myopia and hyperopia treated with cycloplegia showed a statistically insignificant increasing trend of higher order aberrations and spherical aberration. Under natural conditions, the levels of tilt1 aberration, horizontal trefoil and coma7 proved significantly higher in myopia than in hyperopia, while coma8 and tilt2 turned out to be significantly lower than in hyperopia. In myopic eyes, no significant changes were found in any of the examined HOAs after cycloplegiaas compared to the initial state. In contrast, significant changes were found in hyperopia: an increase in horizontal trefoil and a decrease in horizontal coma. An insignificant trend towards an increase in Tilt1 and coma7 and toward a reduction in the vertical trefoil and tilt2 was revaeled. Conclusions. Under natural conditions, a 3-mm wide pupil shows no statistically significant difference between the total level of aberrations of the optical system of the myopic eye and hyperopic eyes in children, while the the wavefront structures in these groups demonstrate essential differences. The differences revealed in the wavefront structure and its dynamics under cycloplegia may indicate differences in the accommodation apparatus, in particular, the ciliary muscles and ligaments of the lens for myopia and hyperopia. For citations: Tarutta E.P., Аrutyunyan S.G., Smirnova T.S. Wavefront aberrations in children with myopia and hyperopia before and after cycloplegia. Russian ophthalmological journal. 2017; 10 (3): 78-83. doi: 10.21516/2072-0076-2017-10-3-78-83 (in Russian).